2014
DOI: 10.1016/j.hrthm.2013.11.021
|View full text |Cite
|
Sign up to set email alerts
|

A KCNQ1 mutation contributes to the concealed type 1 long QT phenotype by limiting the Kv7.1 channel conformational changes associated with protein kinase A phosphorylation

Abstract: BACKGROUND Type 1 long QT syndrome (LQT1) is caused by loss-of-function mutations in the KCNQ1-encoded Kv7.1 channel that conducts the slowly activating component of the delayed rectifier K+ current (IKs). Clinically, the diagnosis of LQT1 is complicated by variable phenotypic expressivity, whereby approximately 25% of genotype-positive individuals present with concealed LQT1 (resting corrected QT [QTc] interval ≤ 460 ms). OBJECTIVE To determine whether a specific molecular mechanism contributes to concealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…, ; Bartos et al . ). The ISO‐ and Ca 2+ ‐dependent changes in I Ks biophysical properties are similar, and these effects may influence the voltage‐sensing and pore domains in a comparable fashion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, ; Bartos et al . ). The ISO‐ and Ca 2+ ‐dependent changes in I Ks biophysical properties are similar, and these effects may influence the voltage‐sensing and pore domains in a comparable fashion.…”
Section: Discussionmentioning
confidence: 97%
“…We conclude that β-adrenergic activation is able to stimulate I Ks in a manner independent of [Ca 2+ ] i ; however, the similar (and additive) effects might imply a common molecular shift. Specifically, several studies showed how PKA phosphorylation at S27 on the N-terminus of Kv7.1 leads to a reduction in drug sensitivity suggesting that PKA phosphorylation restricts allosteric drug binding because of changes in the molecular conformation of Kv7.1 (Yang et al 2009(Yang et al , 2013Bartos et al 2014). The ISO-and Ca 2+ -dependent changes in I Ks biophysical properties are similar, and these effects J Physiol 595.7 may influence the voltage-sensing and pore domains in a comparable fashion.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…59 The most important of these are I CaL , already discussed, the slow delayed-rectifier K + -current I Ks , and the inward-rectifier I K1 . I Ks is strongly enhanced by adrenergically-induced PKA-phosphorylation, 60 allowing it to offset the increased inward current resulting from adrenergic enhancement of I CaL and prevent EADs. 61 I K1 is important in setting the resting potential, contributing to repolarization reserve 62 and governing AF-dynamics.…”
Section: Autonomic Regulation Of Atrial Cardiomyocyte Electrophysiologymentioning
confidence: 99%
“…Functionally, IKs is regulated by a number of interacting proteins and posttranslational modifications. [12][13][14][15][16] The IKs currents and the channel subunits KCNQ1 and KCNE1 proteins are regulated by the b-adrenergic-mediated protein kinase A-dependent phosphorylation, a process that might be pathogenic in heart failure. 14,[17][18][19][20] Likewise, IKs are calcium-responsive currents, partly because of interaction of the KCNQ1 with calmodulin, which is a constitutive component of the K + channels.…”
Section: Discussionmentioning
confidence: 99%